A new modulated crystal structure of the ANS complex of the St John's wort Hyp‐1 protein with 36 protein molecules in the asymmetric unit of the supercell. Issue 7 (6th July 2020) - Smietanska, Joanna; Sliwiak, Joanna; Gilski, Miroslaw; Dauter, Zbigniew; Strzalka, Radoslaw; Wolny, Janusz; Jaskolski, Mariusz
Abstract : When crystallized in complex with the fluorescent dye 8‐anilinonaphthalene‐1‐sulfonate (ANS) in the presence of melatonin, Hyp‐1, a pathogenesis‐related class 10 protein from Hypericum perforatum, produced tetartohedrally twinned C 2 crystals with commensurate structure modulation, which was interpreted as a ninefold expansion of the unit cell in the c direction. The asymmetric unit of this supercell contains 36 protein molecules (differently populated by 156 ANS ligands) arranged into columns by a combination of ninefold translational noncrystallographic symmetry and pseudotetragonal rotational NCS. Abstract : Superstructure modulation, with violation of the strict short‐range periodic order of consecutive crystal unit cells, is well known in small‐molecule crystallography but is rarely reported for macromolecular crystals. To date, one modulated macromolecular crystal structure has been successfully determined and refined for a pathogenesis‐related class 10 protein from Hypericum perforatum (Hyp‐1) crystallized as a complex with 8‐anilinonaphthalene‐1‐sulfonate (ANS) [Sliwiak et al. (2015), Acta Cryst. D71, 829–843]. The commensurate modulation in that case was interpreted in a supercell with sevenfold expansion along c . When crystallized in the additional presence of melatonin, the Hyp‐1–ANS complex formed crystals with a different pattern of structure modulation, in which the supercell shows a ninefold expansion of c, manifested in the diffraction pattern by a wave of reflection‐intensity modulation with crests at l = 9 n and l = 9 n ± 4. Despite complicated tetartohedral twinning, the structure has been successfully determined and refined to 2.3 Å resolution using a description in a ninefold‐expanded supercell, with 36 independent Hyp‐1 chains and 156 ANS ligands populating the three internal (95 ligands) and five interstitial (61 ligands) binding sites. The commensurate superstructures and ligand‐binding sites of the two crystal structures are compared, with a discussion of the effect of melatonin on the co‐crystallization process.